2020
DOI: 10.1080/15548732.2020.1814542
|View full text |Cite
|
Sign up to set email alerts
|

It is not a broken system, it is a system that needs to be broken: the upEND movement to abolish the child welfare system

Abstract: The child welfare system disproportionately harms Black children and families through systemic over-surveillance, overinvolvement, and the resulting adverse outcomes associated with foster care. Ending this harm will only be achieved when the forcible surveillance and separation of children from their parents is no longer viewed as an acceptable form of intervention. This paper describes the upEND movement, a collaborative movement aimed at abolishing the child welfare system as we know it and reimagining how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
107
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(108 citation statements)
references
References 35 publications
1
107
0
Order By: Relevance
“…Research has established important links between race, poverty, and the placement of children into foster care (Lanier et al 2014). Some studies have shown that race functions in combination with other factors such as type of abuse (Gryzlak, et al 2005), family structure (Harris & Courtney, 2003), and caseworker’s assessment of risk ( Dettlaf et al, 2020 ). This study demonstrates that overall rates of maltreatment resulting in foster care placement increased for White youth during the Safer-at-Home Order, while rates of placement of due to inadequate supervision, emotional neglect, and/or parental substance use decreased for Black youth during this same period.…”
Section: Discussionmentioning
confidence: 99%
“…Research has established important links between race, poverty, and the placement of children into foster care (Lanier et al 2014). Some studies have shown that race functions in combination with other factors such as type of abuse (Gryzlak, et al 2005), family structure (Harris & Courtney, 2003), and caseworker’s assessment of risk ( Dettlaf et al, 2020 ). This study demonstrates that overall rates of maltreatment resulting in foster care placement increased for White youth during the Safer-at-Home Order, while rates of placement of due to inadequate supervision, emotional neglect, and/or parental substance use decreased for Black youth during this same period.…”
Section: Discussionmentioning
confidence: 99%
“…Results from this study highlight the importance of prioritizing permanency during COVID-19 and pursuing safe ways to reunite foster children with their biological parents, siblings, and other family members. Importantly, the results also speak to the increasing awareness about the harms of family separation in the broader field of child welfare ( Dettlaff et al, 2020 ; Sankaran et al, 2019 ). Foster parents seem to be having related conversations on Reddit and are becoming aware of the negative impacts that family separation may be having on foster children and youth.…”
Section: Discussionmentioning
confidence: 67%
“…As one participant poignantly expressed, “the world shouldn’t be like that.” As service systems and researchers alike strive to recognize and respond to the socioeconomic diversity of emerging adults, it is critical to retain an intersectional lens and acknowledge how forms of oppression including racism, sexism, and heterosexism intersect with socioeconomic disadvantage in varying and multilayered ways. Researchers can play a role in dismantling systemic oppression not only by recognizing its existence and impact on the people and phenomena they study, but also by using research to advocate for change, such as the recent movement to abolish the U.S. child welfare system and reimagine new structures of support aligned with anti-racist principles (Dettlaff et al, 2020).…”
Section: Discussionmentioning
confidence: 99%